Multi-dimensional analysis, 25 years on a tribute to Douglas Biber - Sardinha, Tony Berber; Pinto, Marcia Veirano; Biber, Douglas (Studies in corpus linguistics., 2014)
This research describes a case study from engineering education that explores the potential for integrating Multi-Dimensional (MD) analysis into mixed methods research so that MD analyses can address more specific educational problems. The study investigates a specific problem in civil engineering: the mismatch between students' writing skills and the demands of writing in the workplace. An MD analysis compares a small number of registers of student and practitioner writing, applying the dimensions of variation in English from Biber (1988). Data from interviews with students, faculty, and prac.